종양병동 간호사의 공감피로 및 공감만족에 따른 우울, 불안, 수면장애 - 김성자(Kim, Sung Ja); 나현주(Na, Hyunjoo) (Asian oncology nursing, 2017)
Purpose: This study was conducted to identify the relationships between various factors, including compassion fatigue, compassion satisfaction, depression, anxiety, and sleep disorders among oncology nurses. Methods: A convenience sample of 140 oncology nurses from 3 university hospitals completed questionnaires. The collected data were analyzed using t-tests, ANOVA, Pearson’s correlation coefficients, and Kruskal-Wallis tests. Results: Compassion fatigue is composed of secondary traumatic stress and burnout. The levels of compassion fatigue showed significant positive correlations with depression, anxiety, and sleep disorder. On the other hand, the levels of compassion satisfaction showed significant negative correlations with compassion fatigue, depression, anxiety, and sleep disorders. The subjects in the at-risk and very distressed group of compassion fatigue and compassion satisfaction risk profile had significantly higher levels of depression, anxiety, and sleep disorders. Conclusion: Such efforts will help reduce the level of depression, anxiety, and sleep disorders in oncology nurses at-risk of developing compassion fatigue. It is also necessary to provide organization support for oncology nurses, and to develop an intervention that is designed to mitigate their compassion fatigue and to promote compassion satisfaction. KCI Citation Count: 7